Korelasi dan Analisis Lintas Karakter Agronomi Kedelai (Glycine max [L.] Merrill) Keturunan Persilangan Wilis X MLG 2521 - Nyimas Sa’diyah; Christian Raymond Siagian; Maimun Barmawi (Politeknik Negeri Lampung., 2016)
Soybean is one of the crops that produce seeds with high protein content, as well as used by the inhabitants of Indonesia. Domestic soybean production can not meet the needs of the national soybean thus needs to be improved, one through breeding varieties with superior. One important step in plant breeding is the selection. To save time and costs of selection, it is necessary to determine the estimated correlation between characters and to determine the causal relationship between characters used path analysis. Through path analysis can be seen directly and indirectly influence between variables forecaster with the response variable. The purpose of this study to obtain information (1) correlation between characters agronomic towards production. (2) direct and indirect effects of agronomic between characters towards production. The research was conducted from October 2013 until January 2014 in the integrated field laboratory of the Faculty of Agriculture, University of Lampung and observations made in Laboratory of Seed and Plant Breeding, University of Lampung. Soybean seeds used were F5 generation zuriat from Wilis x Mlg 2521, Willis and Mlg 2521. The treatment laid out in a randomized block design, 2 replications. The results showed that there was a positive phenotype correlation between character of days to flowering, plant height, number of branches, number of pods, weight of 100 grains with grain weight per plant and there was no correlation between day to harvesting with the seed weight per plant. Direct selection of the most effective was through the number of pods because number of pods have a direct effect almost equivalent to the correlation. The relationship between the number of pods and weight of seeds per plant explained a real relationship. Keywords: correlation, path analysis, selection, soybean